2004
DOI: 10.1074/jbc.m400561200
|View full text |Cite
|
Sign up to set email alerts
|

Identification of an Apolipoprotein A-I Structural Element That Mediates Cellular Cholesterol Efflux and Stabilizes ATP Binding Cassette Transporter A1

Abstract: Synthetic peptides were used in this study to identify a structural element of apolipoprotein (apo) A-I that stimulates cellular cholesterol efflux and stabilizes the ATP binding cassette transporter A1 (ABCA1). Peptides (22-mers) based on helices 1 (amino acids 44 -65) and 10 (amino acids 220 -241) of apoA-I had high lipid binding affinity but failed to mediate ABCA1-dependent cholesterol efflux, and they lacked the ability to stabilize ABCA1. The addition of helix 9 (amino acids 209 -219) to either helix 1 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
70
1

Year Published

2004
2004
2011
2011

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(79 citation statements)
references
References 46 publications
8
70
1
Order By: Relevance
“…Cross-linking (37) and synthetic peptide (38) studies have indicated that interaction between apoA-I and ABCA1 is not sequence specific. Analysis of helix pairs, such as 1 and 9 in apoA-I, has shown that an important motif for interaction of many lipoproteins with ABCA1 is the C-terminal hydrophobic patch adjacent to a negative charge cluster (39). Although acidic residues, which are part of the proposed ABCA1 interaction motif, are not known with certainty, it is intriguing that the largest negative patch including contributions from Asp-73 and Glu-78, both part of helix 2, is Ϸ28 Å from the hydrophobic patch on the C-terminal domain; a distance that is close to the Ϸ32 Å estimated to separate similar patches in the helix 1-9 chimera (39).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cross-linking (37) and synthetic peptide (38) studies have indicated that interaction between apoA-I and ABCA1 is not sequence specific. Analysis of helix pairs, such as 1 and 9 in apoA-I, has shown that an important motif for interaction of many lipoproteins with ABCA1 is the C-terminal hydrophobic patch adjacent to a negative charge cluster (39). Although acidic residues, which are part of the proposed ABCA1 interaction motif, are not known with certainty, it is intriguing that the largest negative patch including contributions from Asp-73 and Glu-78, both part of helix 2, is Ϸ28 Å from the hydrophobic patch on the C-terminal domain; a distance that is close to the Ϸ32 Å estimated to separate similar patches in the helix 1-9 chimera (39).…”
Section: Resultsmentioning
confidence: 99%
“…The preponderance of negative charge on the surface results in a predominantly negative potential field surrounding the structure. Electrostatic attraction of apoA-I toward positively charged regions of ABCA1 is hypothesized to be important prelude to their interaction (39). Presence of a negative potential field around apoA-I would assist in the approach and orientation of lipid-free apoA-I for docking with ABCA1.…”
Section: Resultsmentioning
confidence: 99%
“…These are the apoA-I peptides with the greatest ability to interact with lipids (14). These results agree with a recent study that revealed that only those peptides corresponding to apoA-I helices 1, 9, and 10 were efficient at eliciting FC efflux (38). Peptides representing central domains in the apoA-I molecule were completely ineffective in eliciting FC efflux from both types of cells.…”
Section: Fig 4 Relative Cholesterol and Phospholipid Efflux From Fisupporting
confidence: 92%
“…However, the lipid binding capacity could not explain the increased efflux efficiency that A-I(K107C) displayed. A specific arrangement of acidic residues on the ␣ helices was required to mediate cholesterol efflux (45). As a matter of fact, the mutation in A-I(K107C) disrupted the salt bridges between Lys-107 and Asp-103, which might lead to a rearrangement of the amino acids to facilitate efflux.…”
Section: Discussionmentioning
confidence: 99%